2014
DOI: 10.1039/c4ta01709a
|View full text |Cite
|
Sign up to set email alerts
|

Improved cycle stability and high security of Li-B alloy anode for lithium–sulfur battery

Abstract: Li-B alloy has uniform Li deposition morphology and offers better capacity retention as advantageous anode properties over metallic lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 28 publications
(26 reference statements)
2
112
0
Order By: Relevance
“…[ 160,161 ] In comparison with the common metallic Li anode, the Li-B alloy exhibited better performance in preventing dendrite formation. [ 160 ] The Li metal showed serious dendrite growth on the surface after 20 cycles in a Li-S battery, while the Li-B alloy retained a smooth surface under the same test conditions, giving lower impedance than that of the Li metal based cell.…”
Section: Other Alloy-based Anodesmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 160,161 ] In comparison with the common metallic Li anode, the Li-B alloy exhibited better performance in preventing dendrite formation. [ 160 ] The Li metal showed serious dendrite growth on the surface after 20 cycles in a Li-S battery, while the Li-B alloy retained a smooth surface under the same test conditions, giving lower impedance than that of the Li metal based cell.…”
Section: Other Alloy-based Anodesmentioning
confidence: 98%
“…Importantly, the sponge-like framework of the Li-B alloy can be maintained during cycling, resulting in a good cycling stability. [ 161 ] Duan et al [ 160 ] studied the performance of the Li 7 B 6 alloy as an anode in Li-S batteries (see Figure 23 ). Compared with a pure Li metal anode, the Li 7 B 6 alloy anode exhibited slightly improved Li Coulombic effi ciency, and stabilized at about 96% after 25 cycles.…”
Section: Other Alloy-based Anodesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the plating process at a current density of 2 mA cm −2 for preparing the 3D lithium-Cu hybrid, metallic lithium was preferentially deposited onto the surface of Cu skeletons, and the morphology and thickness of the electrode were well maintained. [48] These 3D architectures exhibited a good electrochemical performance in term of high and stable lithium Adv. As a consequence, the 3D lithium-Cu electrode exhibited a high stable and low voltage hysteresis in symmetric cell and exhibited a high Columbic efficiency of 99% and long cycling lifespan in a full cell with LiFePO 4 as cathode.…”
Section: Regulating Electric Fields or Decreasing Effective Current Dmentioning
confidence: 99%
“…Another promising anode instead of metallic lithium is lithium alloys like lithium–boron alloy (Li 7 B 6 ) . Zhang and co‐workers found that the 3D Li 7 B 6 nanostructure enlarged the specific area and then suppressed the dendrite growth by reducing the current density.…”
Section: Anodesmentioning
confidence: 99%